Material Characterization of MR Fluid on Performance of MRF Based Brake - Quoc, Nguyen Vien; Tuan, Le Duy; Hiep, Le Dai; Quoc, Hung Nguyen; Choi, Seung Bok (Frontiers in Materials, 2019)
This study focuses on material characterizations of magneto-rheological fluid (MRF) on performance characteristics of MRF based brake (in short MRB). In this study, three different types of MRF (low viscosity, medium viscosity and high viscosity) are considered for several types of MRB. Firstly, the optimization solution of the MRB design is proposed based on Bingham plastic model of the MRFs and finite element analysis of MRB magnetic circuit. From optimal design of the MRBs with different MRFs, performance characteristics of the MRBs such as braking torque, off-state torque and power consumption are evaluated. In addition, the compact size of MRB using different MRFs is also studied. Finally, some observations and guidance on selection of MRFs in MRB design are summarized.